PELATIHAN TARI DI DESA MANYAREJO SEBAGAI SALAH SATU LANGKAH MENUJU DESA WISATA - Hartanto (Institut Seni Indonesia Surakarta, 2024)
Abstract This report is the result of Community Service entitled “Dance Training in Manyarejo Village as One Step Towards a Tourism Village Tour”. The target of the activity is the people of Krajan Grogolan, Manyarejo Village. The output of the activity is to direct and make participants to be able to develop creativity in the creation of folk dances. The result of this creativity is the creation of the Rempeg Balung Buto dance. The training activities are carried out using the Dialogical method, the Lecture method, the Demonstration method, and the Drill method. The method was developed and integrated with the mental development of the participants. This training is expected to become a routine village activity, especially dance. The participants were able to demonstrate the dance work created by the creativity they had learned, mastering the material by rote and correctly. The output of the dance work “Rempeg Balung Buto” has been performed at the Environmental Day commemoration event at the 2022 Krajan Cultural Market, Gebyar Krajan Kengker 2022 and the fossil Handing Carnival event at the Bukuran Ancient Human Museum 2022. This training provides an understanding of basic creativity, doing works creative, and to document audio-visual so that it can be used as a reference in dance learning for the next generation in society. Keywords: training, creativity, dance, society.